Photoluminescence study of ZnO on porous silicon nanostructure / Suhaidah Amizam - Amizam, Suhaidah (2006)
In this study, porous structures were formed on a p-type of Si wafer by anodization in ethanoic solutions containing aqueous hydrofluoric acid. The parameter for the PSi sample is fixed which are etching time and current density. ZnO deposited onto porous silicon substrates by the sol-gel method were studied. The starting material of the ZnO sol-gel was Zinc acetate. The room temperature photoluminescence (PL) and chemical properties of Psi before and after deposition of ZnO were investigated by using Photoluminescence spectroscopy and Fourier transforms infrared (FTIR) spectroscopy. As prepared PSi emit orange light. The peak position of PSi after deposition of ZnO shifted to blue with a value is around 650 nm. Using the FTIR spectroscopy, we have observed O-H stretch mode for ZnO at 3350 cm¯ᶦ.